(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): What is the impact of knowledge management on the organisational quality? Purpose: The purpose of the research is to conduct a review of domestic and international professional literature, in which the authors addressed the development of organizational thought, quality management within organizations, and the impact of knowledge management. Method: We reviewed and analysed domestic and foreign literature using the databases of Slovenian libraries, as well as the Scopus, Science Direct, and Google Scholar databases. In these sources, we searched for freely accessible scientific articles and monographies. Results: Results showed that knowledge management contributes to more productive and efficient work among employees. Additionally, knowledge management factors positively impact the implementation of improvements, work performance, and job satisfaction. Organization: The research findings are useful for founders and managers within organizations, as the implementation of knowledge management can significantly contribute to improving the quality of operations. Society: Our research confirmed that effective knowledge management is crucial for ensuring high-quality services, which directly impacts the social well-being of the entire population. Originality: In the literature we did not find any research that connect all three paradigms—organizational thought development, quality management, and knowledge management. We find this is the first research in this field, providing a foundation for further investigation. Limitations / further research: Limitations of the research include unrestricted timeframe for data collection. It would be beneficial to limit the literature to specific time periods and compare the differences between these periods in the context of all three paradigms.